Kant’s Appearance as an Objectual Representation - Katrechko, Sergey (Con-Textos Kantianos. International Journal of Philosophy, 2018)
This paper analyses the features of Kant’s transcendental philosophy (or Kant’s transcendentalism), which Kant himself described as transcendental idealism. On the one hand, Kant’s transcendentalism rests on the distinction between things in themselves and appearances. On the other hand, our ‘mode of cognition’ [Critique, B25] cognition is representative in that is based on representations — subjective and objective (objectual) ones. A synthesis of the above considerations suggests that Kant’s transcendentalism rests on the conceptual triad “[objective] object (thing in itself; Ding an sich) — appearance (Erscheinung) — and [mental] representation (Vorstellung)“. Kant’s transcendentalism is impossible without the ‘premise’ of appearance (a paraphrase of Jacobi’s maxim). The correct interpretation of Kant’s transcendental philosophy should keep the double difference of appearance both from thing–in–itself and representation. In this transcendental triad, the Kantian appearance has an intermediate status since it is located between objective things and subjective representations. However, the conceptual (ontological and epistemological) status of the appearance needs to be clarified, since Kant himself does not give a clear answer to this question, and at present there are several interpretations, differing primarily in the definition of the concept of the appearance (the contemporary confrontation of the theory of “two objects” and theory of “two aspects” is a paradigmatic example of it). For me, appearance can be correlated with objective–objectual (gegenstänslich) representation. It would be unwise to identify appearance with thing in itself, which was characteristic of pre–Kantian philosophy (naïve realism), or appearance with representation, which was the case in phenomenalist interpretations of transcendental idealism à la Berkley (theory of ‘two objects’). The Kantian appearance, as emphasised in BXXVII of his Critique, is an appearance of an object, which — although implicitly — suggests a semantic relationship of reference. In this case, the appearance is not an object, but just ‘a designation (or sign) of an object’ [Critique, B235]. Appearance (as a sign) is impossible without what appears in it (the referent of a sign). This paper puts forward a number of arguments in favour of the objectual (objective–objectual) status of Kant’s concept of appearance.